PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER TERHADAP PROFITABILITAS PERUSAHAAN SUB-SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Joshua Hutagaol; Romulo Sinabutar (Jurnal Ekonomis, 2020)
This purpose of this study to determine the effect of current ratio, debt to equity ratio and total asset turnover on profitability. Ten chemical sub-sector companies were used as samples in this study with a period of time of 3 years so the total sample used was as many as 30 samples. Variable testing of research is conducted with t (partial) and f (simultaneous) tests with a significance level (α) of 0.05 or 5%. Multiple linear regressions are used as a method for analyzing research data. This study found that current ratio has a negative and not significant effect on the profitability 0.158>0.05 with t count -1.455, debt to equity ratio has a negative and significant effect on profitability 0.017<0.05 with t count -2.540, and total asset turnover has a positive but not significant effect 0.161>0.05 with t count 1.444.